1953
DOI: 10.1136/thx.8.1.73
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Measure of the Maximum Ventilatory Capacity in Health and Disease

Abstract: The assessment of disability in dust diseases of the lung presents a problem of great practical importance.Available evidence indicates that disturbance of the alveolar respiratory component of pulmonary function is of importance in producing disability only in such diseases as pulmonary sarcoidosis and berylliosis (Ferris, Affeldt, Kriete, and Whitten berger, 1951) where there is a lesion of the alveolar epithelium. Much further work remains to be done before the importance of disturbance of the mixing comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
1
2

Year Published

1954
1954
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 6 publications
1
50
1
2
Order By: Relevance
“…While the "timing of the VC" was progressively overcoming the MBC, much controversy remained about the most convenient time measurement; advocates of 0.75 s [55] or 2 s [56,57] could still be found. SNIDER et al [58] suggested that the 1 s VC was less sensitive than the MBC to demonstrate bronchodilator changes.…”
Section: Historical Notementioning
confidence: 99%
“…While the "timing of the VC" was progressively overcoming the MBC, much controversy remained about the most convenient time measurement; advocates of 0.75 s [55] or 2 s [56,57] could still be found. SNIDER et al [58] suggested that the 1 s VC was less sensitive than the MBC to demonstrate bronchodilator changes.…”
Section: Historical Notementioning
confidence: 99%
“…record-or of some portion of it-with the M.V.C. Kennedy (1953) draws attention to the form of what he terms the E.V.S. tracing and comments that it is never uniform throughout its length, and may, except in certain types of abnormal patients, be divided into two fractions.…”
mentioning
confidence: 99%
“…The position of the dividing point between the first and second fraction, i.e., where the tracing deviates from a straight line, has been termed the critical point (Kennedy, 1950 Clearly it is a matter of considerable importance, both for the theoretical implications and for the validation of any predictions which are to be made from such records, to decide which of these very different kinds of curve is correct, and, if possible, to explain the differences. Kennedy (1953) states that his records were made on a spirometer almost identical with that described by Gilson and Hugh-Jones (1949). From their description, which, unfortunately, is not detailed, it appears that their spirometer was physically similar to the conventional Knipping type of spirometer.…”
mentioning
confidence: 99%
See 2 more Smart Citations